A structural interpretation of the impact of the great recession on the Austrian economy using an estimated DSGE model - Gerhard Fenz; Lukas Reiss; Martin Schneider (Oesterreichische Nationalbank (OeNB), 2012)
In this paper we present an analysis of the impact of the great recession of the years 2008 and 2009 on the Austrian economy. For this purpose, we utilize the new estimated DSGE model of the OeNB for the Austrian economy within the Euro area. This model is a small open-economy version of Smets & Wouters (2003), where the domestic economy is linked to a highly stylized representation of the rest of the Euro area via trade and financial flows. The model identifies foreign demand and confidence shocks as the main transmission channels. Moreover the risk premium shock contributed significantly to the downturn of the Austrian economy. In contrast price shocks (price markup and raw material shocks) were supportive throughout the crisis. The strong resilience of the Austrian labour market during the crisis and the subsequent upswing is reected in a series of negative technology shocks.
Keywords: 330; Konjunktur; Wirkungsanalyse; Schock; Eurozone; Dynamisches Gleichgewicht; Kleine offene Volkswirtschaft; Österreich